Sejarah Sosial Perkembangan Islam di Indonesia - Mannang, Abd.; S, Suhufi; M, Misbahuddin; Alwaris, Sri Ayu Andari Putri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This paper discusses the social history of the development of Islam in Indonesia, tracing the entry of Islam from the 13th century to its development in the social fabric of contemporary Indonesian society. The focus of study includes the role of Islamic merchants, scholars, and kingdoms in spreading this religion as well as the integration of Islamic values into local culture. Through a descriptive qualitative approach, this study utilizes a literature study with cutting-edge academic sources. The study results show that Islam in Indonesia is evolving not only as a religion, but also as a dynamic and adaptive social and cultural force.